2023
DOI: 10.1261/rna.079450.122
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast C-to-U RNA editing in vascular plants is adaptive due to its restorative effect: testing the restorative hypothesis

Abstract: The adaptiveness of nonsynonymous RNA editing (recoding) could be conferred by the flexibility of the temporal-spatially controllable proteomic diversity, or by its restorative effect which fixes unfavorable genomic mutations at the RNA level. These two complementary hypotheses, namely, the diversifying hypothesis and the restorative hypothesis, have distinct predictions on the landscape of RNA editing sites. We collected the chloroplast C-to-U RNA editomes of 21 vascular plants (11 angiosperms, four gymnosper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…As previously stated, the final effect may be an A to G reverse mutation, but the entire process does not improve the organism’s adaptation ( Jiang and Zhang, 2019 ). Additionally, a recent study found that nonsynonymous C-to-U RNA editing is adaptive due to its restorative effects in plants ( Duan et al, 2023 ). On the other hand, some researchers believe that editing is adaptive because it has been discovered that even restored editing events are less prone to mutation than other A sites, which implies that it is evolutionarily deliberate to keep these events rather than reverting to their original state ( Liu et al, 2017 ; Shoshan et al, 2021 ).…”
Section: Adaptive Advantage Of A-to-i Rna Editing In Bacteriamentioning
confidence: 99%
“…As previously stated, the final effect may be an A to G reverse mutation, but the entire process does not improve the organism’s adaptation ( Jiang and Zhang, 2019 ). Additionally, a recent study found that nonsynonymous C-to-U RNA editing is adaptive due to its restorative effects in plants ( Duan et al, 2023 ). On the other hand, some researchers believe that editing is adaptive because it has been discovered that even restored editing events are less prone to mutation than other A sites, which implies that it is evolutionarily deliberate to keep these events rather than reverting to their original state ( Liu et al, 2017 ; Shoshan et al, 2021 ).…”
Section: Adaptive Advantage Of A-to-i Rna Editing In Bacteriamentioning
confidence: 99%
“…ancestral DNA, then it is apparent that the editing mechanism still increases the fitness of the uneditable allele ( Figure 1D ). Under this scenario, this action/process of restorative RNA editing is adaptive (Duan et al, 2023 ).…”
Section: Two Complementary Hypotheses On Adaptive Non-synonymous A-to...mentioning
confidence: 99%
“…On the other hand, the restorative hypothesis requires the ancestral sequence of editing sites to be the post-edited version and that the editing level should be high. Restorative RNA editing typically takes place in plants (Duan et al, 2023 ) and whether it exists in animals is still under debate (Jiang and Zhang, 2019 ; Shoshan et al, 2021 ).…”
Section: Does Non-synonymous Editing In Bacteria Belong To Diversifyi...mentioning
confidence: 99%
“…In contrast, when replication errors (or SNPs) in SARS-CoV-2 are excluded, the remaining SNVs (if any) should belong to RNA editing events. A typical SNV profile of RNA editing should significantly skew to a particular type of mutation, such as A-to-G or C-to-T [ 11 13 ]. Amazingly, even with a symmetric SNV profile in hand, the Di Giorgio et al paper concluded that what they found were RNA editing events.…”
Section: Stage1: the “Trigger” Of This Debatementioning
confidence: 99%